Word and Image: Polish Medieval and Renaissance Religious Writings in the European Context - Kaczor-Scheitler, Katarzyna Agnieszka (Verbum vitae, 2021)
The article presents the Polish religious writing of the Middle Ages and Renaissance as an expression of correspondence between the word and image. It also demonstrates the impact of European graphics, including Albrecht Dürer’s woodcuts, upon Polish religious works of the period (such as the works by Pseudo-Bonaventura in his rendering of Baltazar Opec’s Żywot Pana Jezu Krysta and Jan Sandecki’s Historie biblijne or Rozmyślania dominikańskie. The article also emphasizes that it was Dürer who paved the way for the book illustration, thus turning woodcuts into an art form in their own right. The fifteenth century was a watershed in book culture. As new illustration techniques at the turn of the fifteenth and sixteenth centuries encouraged the growth of illustrated printed books, the codex became obsolete.